Olli & Bucklan$nOlga Gummerus-Ehrström ja Eric O.W. Ehrström - Hänninen, Helena; Hänninen, Helena (Serlachius-museoiden julkaisuja, 2019)
The artist couple Olga Gummerus-Ehrström (1876?1938) and Eric O. W. Ehrström (1881?1934) have remained almost unknown, despite their fine, multifaceted production. Olga (Olli), who studied at the 'Drawing School of the Finnish Art Society' and at academies in Paris, was a gifted portrait painter, and also worked with her husband on the design and execution of stained glass, textiles and other decorative artworks. Eric (Bucklan) was an artist and exponent of the industrial arts who studied under Akseli Gallen-Kallela and in Paris, making his most important works for the office of Gesellius, Lindgren, Saarinen architects. He was a well-known and respected artist when he was still young, but his oeuvre has subsequently attracted little attention. This book is based on extensive research and presents the life and works of this fascinating artist couple